Caesarean section our experience - Geeta Choudhari; Aishwarya Choudhari (Al Ameen Medical College, 2019)
Background: Lower segment caesarean section (LSCS) is the most commonly performed obstetric operation worldwide. It is relatively safe due to advent of modern anaesthesia, improvised surgical techniques, and use of prophylactic antibiotics. Aim: To identify the various indications of lower section caesarean section (LSCS) and estimate their proportion. Materials and Methods: The prospective study was carried out in the department of Obstetrics and Gynaecology, Al Ameen Medical College Vijayapura Karnataka from January 2015 to December 2016. Results: In prospective 100 cases of deliveries, 67% were normal and 33% cases underwent LSCS out of which 20 cases (60.6%) were emergencies and 13 cases (39.4%) were elective. Most common cases occur between 26-30years (46%), followed by 21-25years (43%). 58% cases were primigravida, 28% were second gravida and 13% were 3rd gravida. 63 patients presented at >38 wks while, 30 presented at 34-38 wks. Only 7 came before 34 weeks. Previous LSCS accounted for the highest indication for LSCS at 33.3% i.e. 11 cases, followed by fetal distress and eclampsia at 12.12% each, i.e. 4 cases each. The lowest indication was bad obstetric history at 3% i.e. 1 patient only. Conclusion: Incidence of caesarean section high, so encouragement should be given to trial of labour in selected low risk cases and in Primi patients whenever possible.